Falsifiability of Science and the Transcendentalism of Religion - Jami, Jamil Asghar (Islamic Studies, 2008)
Today we are living in an age when science has had a profound effect on our thinking and behaviour. Almost every sphere of our life has been affected by science to such an extent that we have developed a mistrust of all that is not part of science. Scientific spirit has come to characterise and almost determine our mental attitudes. Thanks to this overwhelming influence of science, it was natural for the modern man to judge the validity of all that he considers true against the touchstone of science. More recently, the word scientific has become a blanket term to denote accuracy and correctness. Unconsciously (and at times even consciously) the adjective scientific is equated with true and perhaps the only true. Today, more than ever, a great many scholars and theists are desperately striving to adapt religion to the advancements and discoveries of science. Scholars belonging to different religions are taking great pride in flaunting the so-called scientific character of their respective religions, not realising that science itself is much given to change and revision. In this apologetic attitude there is a tacit acknowledgement that truth is an exclusive monopoly of science and anything not confirmed by the empirical investigation of science is bound to be untrue. We are hardly aware that this attitude is not doing any service to religion and, more precisely, by vindicating religion through science we are not providing religion very strong bases to rest on. This paper seeks to work out answers to questions such as the following: How much, if any, of the current scientific lore constitutes knowledge? What is the extent to which scientific method can effectively reach? Are there matters that science is not competent to deal with? This paper will demonstrate that science, by nature, is falsifiable and amenable to change whereas religion is not given to these changes. The study also proposes to demonstrate that science is not without its inherent limitations and inner contradictions and much of science itself is based upon relativities and contingencies, and that any attempt to make religion conformable to science or vice versa does good neither to science nor to religion.